HUBUNGAN ANTARA PERSEPSI ATAS MUTU LAYANAN DENGAN KEIKUTSERTAAN BPJS â€œMANDIRIâ€ PADA PASIEN OBSTETRI DI RSUD CILACAP TAHUN 2016 - ., Johariyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Badan Penyelenggara Jaminan Sosial (BPJS) is a public legal entity formed to organize a social security program. This BPJS consists of BPJS Health and BPJS Employment. All residents of Indonesia are required to become health insurance participants managed by BPJS including foreigners who have worked for a minimum of six months in Indonesia and have paid dues. The level of participation of BPJS â€œMandiriâ€ is still low, which is 3.1% of all BPJS participation. The low participation is likely due to the frequent occurrence of news about the dissatisfaction of the service in patients with PBJS payments, the more people worried to become a participant BPJS. The data analysis is done by using SPSS. The data were analyzed two phases.The first stage is to describe theÂ  perceptions of quality of care in patients with BPJS â€œMandiriâ€ payment and own payment. The second stage is a asostiatifÂ  analysis of perception of quality of care by own payment and BPJS Mandiri payment. The results showed that all responden (100%) haveÂ  the perception of service quality in the high category.Â Based on the analysis we find that there is there was no correlation between perceptions of service with the participation BPJS Mandiri.Keywords: participation, BPJS Mandiri, perceptions